Treatment of Industrial Brass Wastes for the Recovery of Copper and Zinc - Kilicarslan, Ayfer; Saridede, Muhlis Nezihi (TAYLOR & FRANCIS INC, 2015)
A combined pyro-hydrometallurgical treatment processes involving leaching, cementation, electrowinning, and melting have been applied to industrial brass wastes, brass ash, and flue dust to recover copper and zinc. In the first stage, the effects of leach parameters on metal recovery ratio were studied. Almost all zinc was dissolved from brass wastes in conditions of 1 M H2SO4, 120 min, 60 degrees C, 400 rpm stirring speed, and 1/10 solid liquid ratio. Negligible amount of copper was also dissolved in the same conditions and this copper could be precipitated by cementation. Pure zinc of 99.4% and 99.5% were produced by electrowinning of purified brass ash and flue dust leach solutions, respectively. Leach residue containing high amount of copper was melted with various fluxes and more than 99% of copper recovery ratio was achieved.
Keywords: zinc; hydrometallurgy; leach; copper; recovery; brass; HYDROMETALLURGICAL RECOVERY; Chemistry; Engineering